Customers’ Perception on Green Banking Practices in Commercial Banks of Kathmandu, Nepal - Dangol, Shristi; Siddique, Majibur Rahman (Quest Journal of Management and Social Sciences, 2026)
Background: In recent years, the concept of green banking has gained increasing attention as banks attempt to reduce environmental impact through digital banking services, paperless transactions, green loans, and energy-efficient operations. In developing countries like Nepal, the adoption of green banking practices is still emerging, particularly in urban areas such as Kathmandu Valley where commercial banks play a significant role in promoting sustainable financial practices. Purpose: Green banking is becoming increasingly popular among banks and financial organizations due to increased public interest in environmental issues. This study aims to examine the perspectives of customers of commercial banks in Kathmandu valley. Design/methodology /approach: This study used an explanatory research approach to evaluate the factors that influence customers' perception of green banking products as well as analyze its determinants. The study applies both descriptive and inferential analysis. Under descriptive, awareness level is determined and for inferential analysis ordered logistic model was used. The study area was Kathmandu valley and sample population was banking customers. Findings: The study shows that customers are moderately aware of green banking. Key determinants of perception include training, social responsibility, resource waste reduction, environmental regulation, bank policies, green money market, power equipment, and solar energy. Preferred strategies are ethical banking, green loans, green saving accounts, online banking, and solar energy use. Conclusion: This study concludes that banking customers are moderately aware of green banking services which hints that there are more-green banking products can be developed and introduced to consumers. Various studies on customer perception and green banking practices have been conducted, according to author’s knowledge. As a matter of fact, there is no conflict of knowledge and the work is original. Key words: Customer perception, green banking, environment, Kathmandu valley, ordinary logit model